Factors Influencing Generation Z’s Loyalty in Mobile Internet Usage - Rizky Hafizhah Putri; Hartoyo; Sri Hartono (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Generation Z is a valuable target market for the cellular telecommunications industry due to their digital-native behavior. However, their loyalty is a challenge, making it important to understand the factors that influence their loyalty to these services.Purpose: The purpose of this study was to analyze the factors that influence the loyalty of generation Z in using cellular internet services. Design/methodology/approach: The sampling technique used non-probability sampling with a voluntary sampling approach. Data was analyzed using the SEM-PLS model using SmartPLS version 4. Total 146 samples are collected by online form submissions.  Finding/Result: The results of the Structural Equation Modeling (SEM) analysis show that customer satisfaction and trust have a direct effect on Generation Z customer loyalty in using mobile internet services. Meanwhile, other variables such as service quality and brand image have an indirect effect through mediation of customer satisfaction. This finding confirms the important role of customer satisfaction as a mediator in building customer loyalty.Conclusion: Companies should offer extra services that match Generation Z's mobile internet habits to boost satisfaction and loyalty. Using virtual assistants to handle their complaints can also help maintain customer satisfaction.Originality/value (State of the art):  This research focus on analyze Generation Z behavior as the active user of mobile internet providers. Keywords: customer loyalty, customer satisfaction, generation Z, mobile internet, SEM-PLS